Use of in‐stream cover types by adult banded kokopu ( Galaxias fasciatus ) in first‐order North Island, New Zealand, streams - David K. Rowe; Joshua Smith (New Zealand Journal of Marine and Freshwater Research, 2003)
The relative importance of wood material in providing in‐stream cover for adult banded kokopu ( Galaxias fasciatus ) was determined in first‐order, North Island, New Zealand, streams. Three groups of streams, each differing in the relative amount of three types of in‐stream cover (i.e., wood, boulders, undercut banks) were selected and banded kokopu were sampled in their pools using electric fishing. Banded kokopu occurred beneath boulders, undercut banks, and wood material in all pools except those lacking any in‐stream cover, or those where large (total length >400 mm) eels were present. Their presence in pools was therefore highly dependent on in‐stream cover, provided large eels were absent. In streams where the cover provided by boulders was lacking, banded kokopu selected mainly undercut banks and wood. However, in streams containing large amounts of bank and boulder cover, wood was under‐utilised, indicating that it was least preferred. In pools providing a choice of cover types, bank cover was more frequently used than other types, indicating that it is preferred. The mean size of banded kokopu in pools was positively related to their relative abundance, and their abundance was in turn related to habitat quality as defined by in‐stream cover. Streams with the least amount of bank cover had the lowest number of pools occupied by banded kokopu, fewer banded kokopu per pool, fewer pools containing two or more banded kokopu, and the smallest banded kokopu. Collectively, these data indicate that bank cover in pools provides optimal habitat for banded kokopu, and that wood material was important only where other types of more permanent cover were lacking. Logs and wood slash from logging operations could therefore be important for increasing banded kokopu habitat in logged streams where bank and boulder cover are scarce.

Effects of logging with and without riparian strips on fish species abundance, mean size, and the structure of native fish assemblages in Coromandel, New Zealand, streams - David K. Rowe; Joshua Smith; John Quinn; Ian Boothroyd (New Zealand Journal of Marine and Freshwater Research, 2002)
We determined the effects of logging, both with and without a riparian buffer strip, on the native fish fauna at 27 stream sites in an exotic pine (mainly Pinus radiata) forest on the Coromandel Peninsula, New Zealand. Fish abundance at the logged sites was compared with reference sites in both unlogged pine and native forest. The abundance of Anguilla dieffenbachii (Gray) and Anguilla australis (Richardson) was not significantly affected by logging. However, the abundance of Galaxias fasciatus (Gray) and Gobiomorphus huttoni (Ogilby) was. There were fewer Ga. fasciatus at the logged sites without buffers than at the reference sites, but more at the logged sites with buffers. The abundance of Go. huttoni was higher at the logged sites than at the reference sites, and was highest at the logged sites with riparian buffers. Overall, the different, species‐specific responses to logging maximised total fish numbers at the logged sites. As total fish numbers, the abundance of Ga. fasciatus , and species equitability, a measure of fish assemblage structure, were all highest at the logged sites with riparian buffer strips, we concluded that riparian strips enhanced the native fish community of streams within these logged catchments.

Effects of turbidity on the feeding ability of adult, riverine smelt ( Retropinna retropinna) and inanga ( Galaxias maculatus) - David K. Rowe; Joshua Smith; Erica Williams (New Zealand Journal of Marine and Freshwater Research, 2002)
Laboratory tank experiments indicated that turbidity levels up to 160 Nephelometric Turbidity Units (NTU) did not reduce the feeding rates of adult smelt ( Retropinna retropinna Richardson), or inanga (Galaxias maculatus Jenyns), on Daphnia sp. Mean feeding rates were higher for inanga than for smelt. However, the lower rates for smelt were related to the greater variation in individual feeding rates. Specifically, a few fish fed intensively while most did not. As the feeding ability of both species was unaffected by turbidity levels up to 160 NTU, they were less sensitive to turbidity than juvenile banded kokopu ( Galaxias fasciatus Gray). Juvenile banded kokopu should therefore be used as the benchmark species for setting turbidity guidelines to protect native fish in rivers where this species is present. Both juvenile and adult rainbow trout ( Oncorhynchus mykiss Richardson) appear to be more sensitive to turbidity than adult inanga and smelt, so should be used as benchmark species in all other waters.